A method for electrochemical mechanical polishing of semiconductor silicon wafer

By optimizing the electrolyte solution formula and polishing pad material, combined with plasma treatment technology, the problems of uneven polishing and environmental pollution in semiconductor silicon wafer electrochemical mechanical polishing technology are solved, and efficient and environmentally friendly polishing effect is achieved.

CN119121368BActive Publication Date: 2025-02-18SHENZHEN XINDEPU TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411606040.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing semiconductor silicon wafer electrochemical mechanical polishing technology has problems of uneven polishing and great environmental impact when dealing with large-area silicon wafers. In addition, traditional electrolyte solutions are difficult to control surface quality and have great challenges in process consistency.

Method used

The optimized electrolyte solution formula, including citric acid, sodium sulfate, sodium gluconate and sodium phosphate, is used to form a uniform oxide layer with appropriate amounts of synergists, lanthanum nitrate, titanium dioxide and chitin. At the same time, high-performance materials such as polyether ether ketone, polyimide, and polyphenylene sulfide are used to prepare polishing pads, and the surfactivity of the polishing pads is improved through plasma treatment technology.

Benefits of technology

It significantly improves the flatness and polishing quality of the silicon wafer surface, reduces surface defects and environmental pollution, enhances the environmental protection and sustainability of the process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121368B_ABST
    Figure CN119121368B_ABST
Patent Text Reader

Abstract

The present invention provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, belonging to the field of semiconductor manufacturing technology. The method comprises cleaning the silicon wafer with ultrapure water and acetone and drying it with nitrogen, and then preparing an electrolyte solution containing citric acid, sodium sulfate, sodium gluconate, sodium phosphate, surfactant, synergist, lanthanum nitrate, titanium dioxide, chitin and deionized water; fixing the silicon wafer on a polishing head, using a polishing pad with evenly distributed through holes, setting the current density, polishing time and polishing table rotation speed, and starting the polishing program. The present invention effectively improves the flatness of the silicon wafer surface, reduces surface defects, improves the polishing quality and efficiency, reduces production costs, and enhances the environmental protection and sustainability of the process by optimizing the electrolyte solution formula, polishing process parameters and the preparation method of the polishing pad.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor manufacturing, and in particular relates to an electrochemical mechanical polishing method for a semiconductor silicon wafer. Background Art

[0002] With the rapid development of information technology, semiconductor devices are constantly evolving towards higher integration and smaller size. As one of the core materials of integrated circuits, the surface quality of semiconductor silicon wafers directly affects the performance and reliability of the devices. In order to meet increasingly stringent manufacturing requirements, higher standards are put forward for the flatness and smoothness of the silicon wafer surface. Although the traditional chemical mechanical polishing (CMP) technology can meet these requirements to a certain extent, the problems of CMP technology gradually emerge when dealing with finer feature sizes. These problems mainly include surface residual stress, surface damage, particle contamination, etc., especially the problem of uneven polishing is particularly prominent.

[0003] Electrochemical Mechanical Polishing (ECMP) is an emerging surface treatment technology that has been widely studied and applied in recent years. ECMP technology combines the advantages of electrochemical polishing (ECP) and chemical mechanical polishing (CMP). It can selectively remove the defect layer on the surface of the material by electrochemical reaction, and further improve the surface flatness by mechanical force, thereby obtaining a higher quality silicon wafer surface.

[0004] The invention patent with announcement number CN111128712B and classification number H01L21 / 306 discloses a method for metal-assisted chemical etching and polishing silicon wafers. It discloses that the basic principle of the metal-assisted chemical etching method is to spontaneously carry out a primary battery reaction in metal particles / etchant / silicon. Commonly used metal particles include precious metal materials such as Au, Ag, and Pt. The present invention mainly uses Ag as an example for illustration; Ag particles are used as cathodes to undergo reduction reactions, and silicon wafers are used as anodes to undergo oxidation reactions. As the reaction continues, the silicon wafer is polished; the present invention uses Ag particles (50nm to 1mm) and adds stirring conditions in the experiment, so that the Ag particles and the uneven silicon wafer are stirred and rotated together in the etchant. During the rotation process, the protruding parts of the silicon wafer will be etched when they come into contact with the Ag particles, thereby achieving the purpose of polishing.

[0005] The invention patent with the announcement number CN114628252B and the classification number H01L21 / 306 discloses an alkali polishing method for silicon wafers, a PERC cell and a preparation method thereof. The alkali polishing method for silicon wafers recorded therein includes: pre-cleaning, alkali polishing, post-cleaning, pickling, slow pulling and drying steps; wherein the alkali polishing liquid in the first batch of alkali polishing treatment is the initial alkali polishing liquid, and the alkali polishing liquid in the alkali polishing treatment of the nth batch is prepared by adding a replenishing liquid to the alkali polishing liquid of the n-1th batch; the initial alkali polishing liquid includes The volume ratio of water, alkali solution and alkali polishing additive is (320-340): (9.5-12.5): (2.5-3.5); the ratio of water, alkali solution and alkali polishing additive in the replenishing solution is (5.5-6.5): (0.24-0.28): (0.17-0.20); by adjusting the formula of the alkali polishing solution, the weight loss of silicon wafers in the alkali polishing method of silicon wafers is small, the weight loss of silicon wafers by alkali polishing can be reduced, the fragmentation rate in the preparation process is reduced, and the back polished surface of the silicon wafer after alkali polishing is bright and flat.

[0006] Although ECMP technology has shown great potential in improving the surface quality of semiconductor silicon wafers, it still faces some challenges and problems in practical applications: (1) Uniformity issues: During the polishing process of large-area silicon wafers, due to the influence of factors such as current distribution and electrolyte flow, the surface polishing may be uneven, especially in the edge area, where over-polishing or under-polishing is prone to occur. (2) Environmental issues: Although ECMP produces less waste than traditional CMP, it still has certain environmental impacts, especially some chemicals contained in the electrolyte may cause potential harm to the environment. (3) Surface damage: Although ECMP is designed to reduce surface damage caused by mechanical polishing, in some cases, if it is not properly controlled, it may still cause surface defects or damage. (4) Process consistency: In order to ensure that each batch of silicon wafers can meet the same surface quality standards, strict process control measures are required, which is a challenge for large-scale production.

[0007] In the electrochemical mechanical polishing process, the properties of the electrolyte solution have a crucial influence on the polishing effect. The electrolyte solution not only determines the speed of material removal, but also affects the surface quality. Traditional electrolyte solutions usually contain strong acids or strong bases, as well as some additives that can accelerate the dissolution of materials. However, this type of electrolyte solution has certain safety hazards during use and has certain negative impacts on the environment. In addition, due to the complex chemical properties of the surface of semiconductor silicon wafers, traditional electrolyte solutions often find it difficult to achieve uniform polishing of the silicon wafer surface. Therefore, the development of a new, environmentally friendly electrolyte solution that can effectively improve polishing efficiency and surface quality has become an urgent problem to be solved.

[0008] On the other hand, as an important component in the electrochemical mechanical polishing process, the polishing pad's material and structure directly affect the polishing effect. Traditional polishing pad materials are usually polymers or inorganic materials. Although these materials have certain wear resistance and elasticity, they are prone to wear after long-term use, resulting in a decrease in polishing quality. In addition, the traditional polishing pad has a single structure and is difficult to adapt to the polishing requirements of different silicon wafer surfaces. Therefore, finding a new type of polishing pad material with higher wear resistance and better adaptability, and designing a reasonable structure, has become one of the important ways to improve the polishing effect.

[0009] In summary, although the existing semiconductor silicon wafer polishing technology can meet the current needs to a certain extent, it still faces many challenges in meeting the requirements of future higher-end semiconductor device manufacturing. Therefore, the development of a new, efficient and environmentally friendly semiconductor silicon wafer electrochemical mechanical polishing method has important theoretical significance and application value. Summary of the invention

[0010] The purpose of the present invention is to provide a method for electrochemical mechanical polishing of semiconductor silicon wafers, which improves the polishing quality and efficiency of semiconductor silicon wafers, reduces production costs, enhances the environmental protection and sustainability of the process, and has important theoretical significance and application value.

[0011] In order to achieve the above object, the present invention provides the following technical solutions:

[0012] A method for electrochemical mechanical polishing of a semiconductor silicon wafer comprises the following steps:

[0013] (1) Use ultrapure water and acetone to clean the silicon wafer. After cleaning, use nitrogen to blow dry the surface of the silicon wafer to ensure that the surface is clean;

[0014] (2) Prepare electrolyte solution;

[0015] (3) Fix the silicon wafer on the polishing head of the electrochemical mechanical polisher, with the surface to be polished facing the polishing table, lay the polishing pad with evenly distributed through holes on the polishing table, set the current density and polishing time, and adjust the rotation speed of the polishing table to ensure good contact between the silicon wafer and the polishing pad;

[0016] (4) Turn on the power, start the polishing program, spray the electrolyte solution onto the surface of the polishing table, ensure that the electrolyte solution evenly covers the surface of the polishing pad and fills the through holes of the polishing pad to contact the surface of the polishing table, lower the polishing head, immerse the surface of the silicon wafer in the electrolyte solution and form an electrical contact with the polishing table, the silicon wafer and the electrolyte solution undergo an electrochemical reaction to form an oxide layer on the surface of the silicon wafer, start the rotation function of the polishing table, make the polishing head and the polishing table rotate relative to each other to perform grinding and polishing to remove the oxide layer;

[0017] (5) After polishing, use deionized water to clean the surface of the silicon wafer to remove the residual electrolyte solution, and use nitrogen to blow dry the surface of the silicon wafer to prevent moisture from remaining.

[0018] Furthermore, the current density is 10-200 mA / cm², the polishing time is 10-60 minutes, and the rotation speed of the polishing table is 50-500 rpm.

[0019] Furthermore, the electrolyte solution contains the following raw materials in parts by mass: 50-60 parts of electrolyte, 1-3 parts of surfactant, 2-4 parts of synergist, 0.06-0.1 parts of lanthanum nitrate, 0.1-0.5 parts of titanium dioxide, 0.5-1 parts of chitin, and 450-550 parts of deionized water.

[0020] The electrolytes are citric acid, sodium sulfate, sodium gluconate and sodium phosphate, and the mass ratio thereof is 20:(15-25):(7-10):(3-5).

[0021] The surfactant is sodium lauryl sulfate and polyvinyl alcohol, and the mass ratio thereof is 1:0.3-0.5.

[0022] The synergist is polyethylene glycol and sodium silicate, and the mass ratio thereof is 1:1.5-3.

[0023] The present invention optimizes the electrolyte solution, effectively improves the flatness of the silicon wafer surface, reduces surface defects, and ensures that the final polishing effect meets expectations by controlling the formation of the oxide layer. Specifically, citric acid can react with the silicon surface in an electrochemical environment to promote the formation of the oxide layer. Compared with commonly used hydrochloric acid, sulfuric acid, etc., citric acid has a strong buffering effect, which can more easily control the pH value during the polishing process, thereby achieving accurate control of the oxide layer thickness and material removal rate; citric acid can form a stable complex with metal ions, which helps to prevent metal ions from re-depositing on the silicon wafer surface and reduce surface defects; the acidity of citric acid is relatively mild, which can reduce non-selective corrosion on the silicon wafer surface and avoid uneven corrosion on the surface. The presence of sodium sulfate can assist citric acid in promoting the formation of the oxide layer because it can provide the necessary ion concentration to make the electrochemical reaction more stable and controllable. Sodium phosphate has a buffering effect, which can adjust the pH value of the solution and maintain a suitable acid-base environment, which is crucial for the formation and stability of the oxide layer. In addition, sodium gluconate and sodium phosphate can also be used as complexing agents to form stable complexes with metal ions on the silicon surface to prevent metal ions from re-depositing and reduce surface defects. The joint use of polyethylene glycol and sodium silicate can optimize the fluidity of the electrolyte solution, so that it can be evenly distributed during the polishing process and reduce the phenomenon of local over-polishing; the combination of the two can also synergistically adjust the viscosity of the electrolyte solution. Polyethylene glycol increases the viscosity, while the gel-like substance formed by sodium silicate can further enhance the adhesion of the polishing liquid, so that it can better cover the surface of the silicon wafer; in addition, sodium silicate can react with the oxide on the silicon surface to promote the formation of the oxide layer. At the same time, the presence of polyethylene glycol can act as a lubricant to reduce the friction between the silicon wafer and the polishing pad, thereby contributing to the uniform formation of the oxide layer. Lanthanum nitrate can promote the formation of the oxide layer, and due to its special chemical properties, it can improve the stability of the oxide layer, help improve the surface flatness and reduce surface defects. Titanium dioxide can be used as an abrasive to participate in the mechanical polishing process and improve the polishing efficiency. It can also be used as a catalyst to promote the occurrence of electrochemical reactions. Chitin has biocompatibility and good film-forming properties. It can form a protective film on the silicon surface, reduce surface defects, and help control the formation of the oxide layer.

[0024] Furthermore, the surface of the polishing pad has a plurality of evenly distributed through holes, which run through the entire thickness direction of the polishing pad, and the horizontal cross-sectional area of ​​the through holes is 8-15 mm 2 .

[0025] Furthermore, the preparation method of the polishing pad comprises the following steps:

[0026] (1) dispersing carbon nanotubes in a polyetheretherketone (PEEK) melt, and using ultrasonic treatment to ensure that the carbon nanotubes are evenly distributed in the melt, thereby obtaining a polymer melt 1; dispersing graphene nanosheets in a polyimide (PI) melt, and using ultrasonic treatment to ensure that the graphene nanosheets are evenly distributed in the melt, thereby obtaining a polymer melt 2; dispersing nanosilicon dioxide in a polyphenylene sulfide (PPS) melt, and using a high-speed stirrer to stir the nanosilicon dioxide so that the nanosilicon dioxide is evenly distributed in the melt, thereby obtaining a polymer melt 3;

[0027] (2) mixing polymer melt 1, polymer melt 2, and polymer melt 3, and extruding them through a twin-screw extruder to obtain a composite sheet;

[0028] (3) Use a high-precision laser punching machine to punch evenly distributed through holes on the composite sheet. The horizontal cross-sectional area of ​​the through holes is 8~15 mm 2 ;

[0029] (4) The surface of the composite plate with through holes is activated by using plasma treatment technology to obtain the polishing pad.

[0030] Furthermore, the mass proportion of the carbon nanotubes in the polyetheretherketone melt is 0.3-0.6%, the mass proportion of the graphene nanosheets in the polyimide melt is 0.3-0.6%, and the mass proportion of the nano-silicon dioxide in the polyphenylene sulfide melt is 1-3%.

[0031] Furthermore, the mass ratio of the polymer melt 1, the polymer melt 2, and the polymer melt 3 is 1:0.7~0.9:0.7~0.9.

[0032] Furthermore, the conditions of the plasma treatment are set as follows: the gas is oxygen, the gas flow rate is 30-60 sccm, the vacuum degree is 0.5-5 Pa, the power is 200-600 W, and the treatment time is 5-20 minutes.

[0033] The polishing pad of the present invention selects polyetheretherketone (PEEK), polyimide (PI), and polyphenylene sulfide (PPS) as the base material. All three materials have excellent mechanical strength and chemical corrosion resistance, so that the polishing pad can withstand high pressure and is not easy to be damaged. In addition, the characteristics of the three materials can cooperate with each other to further improve the performance of the materials. Specifically, the self-lubricating property of PEEK combined with the high toughness of PI can reduce the friction between the silicon wafer and the polishing pad, thereby reducing surface scratches and damage; the high dielectric property of PI helps to control the current distribution in the electrochemical reaction, and the conductivity of PEEK can promote the uniform transmission of current. The combination of the two can improve the efficiency and accuracy of electrochemical mechanical polishing; the excellent wear resistance and dimensional stability of PPS help to reduce the damage caused by friction during the polishing process, and keep the shape of the polishing pad unchanged during use, which is very important for maintaining the consistency of the polishing effect. The addition of carbon nanotubes, graphene nanosheets and nano-silicon dioxide can further improve the mechanical strength and conductivity of the polishing pad, so that the polishing pad can withstand greater pressure during the polishing process, while ensuring the uniform distribution of current, which helps to improve the surface flatness. Using plasma treatment technology to activate the surface of the polishing pad can enhance its surface activity, increase the surface energy of the polishing pad, and improve its contact with the electrolyte solution, thereby reducing surface defects and improving the polishing effect.

[0034] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0035] The present invention provides a semiconductor silicon wafer electrochemical mechanical polishing method, which significantly improves the flatness of the silicon wafer surface and reduces surface defects by optimizing the electrolyte solution formula, polishing pad material and polishing process parameters, thereby improving the polishing quality and efficiency. The optimized electrolyte solution formula not only contains ingredients such as citric acid, sodium sulfate, sodium gluconate and sodium phosphate, but also adds appropriate amounts of synergists, lanthanum nitrate, titanium dioxide, chitin and other additives. These ingredients work together to promote the formation of a uniform oxide layer, making the oxide layer easy to remove while also improving the surface flatness. In addition, the innovatively designed polishing pad uses high-performance materials such as polyetheretherketone, polyimide, polyphenylene sulfide, and the like, and improves the surface activity through plasma treatment technology, further improves the contact between the polishing pad and the electrolyte solution, and reduces surface defects. The present invention not only improves the polishing efficiency and quality, but also reduces the potential harm to the environment by reducing the use of strong acidic substances, enhances the environmental protection and sustainability of the process, and is suitable for occasions with strict requirements on the surface quality of semiconductor silicon wafers in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of an electrochemical mechanical polisher.

[0037] Figure numerals: 1 - polishing head, 2 - silicon wafer, 3 - polishing pad, 4 - through hole on the polishing pad, 5 - polishing table. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The electrochemical mechanical polisher was purchased from Huahai Qingke Co., Ltd., model HCMS-300A;

[0040] Lanthanum nitrate was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0041] Titanium dioxide was purchased from Shanghai Jinlan Chemical Co., Ltd., with a particle size of 15-25 nm;

[0042] Polyetheretherketone was purchased from Evonik Industries, VESTAKEEP® G;

[0043] Polyimide was purchased from Beijing Shenyu Aerospace Materials Technology Co., Ltd., Kapton HN;

[0044] Polyphenylene sulfide was purchased from Zhejiang Juhua Co., Ltd., Ryton R-4-230;

[0045] Carbon nanotubes were purchased from Nanjing Xianfeng Nanomaterials Technology Co., Ltd., CNTs-MWCNTs-1000;

[0046] Graphene nanosheets were purchased from Ningbo Moxi Technology Co., Ltd., MXene Graphene Nanosheets;

[0047] Nano-silicon dioxide was purchased from Anhui Guibao Technology Co., Ltd., AEROSIL R974.

[0048] Example 1

[0049] This embodiment provides an electrolyte solution, comprising the following raw materials in parts by weight: 56 parts of electrolyte, 2 parts of surfactant, 3 parts of synergist, 0.09 parts of lanthanum nitrate, 0.3 parts of titanium dioxide, 0.6 parts of chitin, and 500 parts of deionized water;

[0050] The electrolytes are citric acid, sodium sulfate, sodium gluconate and sodium phosphate, with a mass ratio of 20:20:8:4; the surfactants are sodium dodecyl sulfate and polyvinyl alcohol, with a mass ratio of 1:0.4; and the enhancers are polyethylene glycol and sodium silicate, with a mass ratio of 1:2.

[0051] Example 2

[0052] This embodiment provides a polishing pad, and the preparation method thereof comprises the following steps:

[0053] (1) Dispersing carbon nanotubes in a polyetheretherketone (PEEK) melt at a mass ratio of 0.4%, and using ultrasonic treatment to ensure that the carbon nanotubes are evenly distributed in the melt, thereby obtaining polymer melt 1; dispersing graphene nanosheets in a polyimide (PI) melt at a mass ratio of 0.5%, and using ultrasonic treatment to ensure that the graphene nanosheets are evenly distributed in the melt, thereby obtaining polymer melt 2; dispersing nano-silicon dioxide in a polyphenylene sulfide (PPS) melt at a mass ratio of 2%, and using a high-speed stirrer to stir the nano-silicon dioxide evenly in the melt, thereby obtaining polymer melt 3;

[0054] (2) mixing polymer melt 1, polymer melt 2, and polymer melt 3 in a mass ratio of 1:0.8:0.8, and extruding the mixture through a twin-screw extruder to obtain a composite sheet;

[0055] (3) Use a high-precision laser punching machine to punch evenly distributed through holes on the composite sheet. The horizontal cross-sectional area of ​​the through holes is 10 mm. 2 ;

[0056] (4) The surface of the composite plate with through holes is activated by plasma treatment technology to obtain the polishing pad; the conditions of the plasma treatment are set as follows: the gas is oxygen, the gas flow rate is 40 sccm, the vacuum degree is 1 Pa, the power is 300 W, and the treatment time is 10 minutes.

[0057] Example 3

[0058] This embodiment provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, using a common commercially available electrochemical mechanical polishing machine, such as the attached Figure 1 As shown, 1 is a polishing head, 2 is a silicon wafer, 3 is a polishing pad, 4 is a through hole on the polishing pad, and 5 is a polishing table.

[0059] The polishing method comprises the following steps:

[0060] (1) Use ultrapure water and acetone to clean the silicon wafer. After cleaning, use nitrogen to blow dry the surface of the silicon wafer to ensure that the surface is clean;

[0061] (2) preparing an electrolyte solution according to the method of Example 1;

[0062] (3) Fix the silicon wafer on the polishing head of an electrochemical mechanical polisher with the surface to be polished facing the polishing table, spread a polishing pad with evenly distributed through holes on the polishing table, set the current density to 100 mA / cm², the polishing time to 30 minutes, and adjust the rotation speed of the polishing table to 300 rpm to ensure good contact between the silicon wafer and the polishing pad; the polishing pad is prepared by the method of Example 2;

[0063] (4) Turn on the power, start the polishing program, spray the electrolyte solution onto the surface of the polishing table, ensure that the electrolyte solution evenly covers the surface of the polishing pad and fills the through holes of the polishing pad to contact the surface of the polishing table, lower the polishing head, immerse the surface of the silicon wafer in the electrolyte solution and form an electrical contact with the polishing table, the silicon wafer and the electrolyte solution undergo an electrochemical reaction to form an oxide layer on the surface of the silicon wafer, start the rotation function of the polishing table, make the polishing head and the polishing table rotate relative to each other to perform grinding and polishing to remove the oxide layer;

[0064] (5) After polishing, use deionized water to clean the surface of the silicon wafer to remove the residual electrolyte solution, and use nitrogen to blow dry the surface of the silicon wafer to prevent moisture from remaining.

[0065] Comparative Example 1

[0066] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that the electrolyte in the electrolyte solution is replaced with sulfuric acid, phosphoric acid and hydrofluoric acid in a mass ratio of 2:1:0.1.

[0067] Comparative Example 2

[0068] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that the synergist in the electrolyte solution is replaced by propylene glycol and sodium carboxymethyl cellulose in a mass ratio of 1:2.

[0069] Comparative Example 3

[0070] This comparative example provides a method for electrochemical mechanical polishing of a semiconductor silicon wafer, which is different from Example 3 in that the electrolyte solution does not contain lanthanum nitrate.

[0071] Comparative Example 4

[0072] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that chitin in the electrolyte solution is replaced by aluminum oxide.

[0073] Comparative Example 5

[0074] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that polyetheretherketone, polyimide and polyphenylene sulfide in the polishing pad are replaced by polyurethane, polyethylene and polyvinyl alcohol, respectively.

[0075] Comparative Example 6

[0076] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that the graphene nanosheets and nano-silicon dioxide in the polishing pad are replaced with carbon nanotubes.

[0077] Comparative Example 7

[0078] This comparative example provides a method for electrochemical mechanical polishing of semiconductor silicon wafers, which differs from Example 3 in that the plasma treatment in step (4) of preparing the polishing pad is replaced by immersing the composite plate with through holes in a 5 wt % potassium persulfate aqueous solution for 30 minutes, then washing it with deionized water and drying it naturally.

[0079] Performance Test 1 Surface Roughness Measurement

[0080] Testing instrument: profilometer;

[0081] Test sample: semiconductor silicon wafer polished by the methods of Example 3 and Comparative Examples 1-7;

[0082] Test method: Use ultrapure water and acetone to clean the silicon wafer to ensure that there are no impurities on the surface; use standard samples to calibrate the profilometer; place the silicon wafer on the measurement platform, set the scanning range and resolution to ensure that the surface features at different scales are captured; collect data and calculate the surface roughness parameter Ra. The test results are shown in Table 1.

[0083] Table 1 Surface roughness measurement results

[0084]

[0085] The above measurement results show that Example 3 exhibits the best polishing effect and the lowest surface roughness. In Comparative Example 1, since the electrolyte in the electrolyte solution is replaced by sulfuric acid, phosphoric acid and hydrofluoric acid, these three acids are highly corrosive, especially in an electrochemical environment, which may cause uneven corrosion on the surface of the silicon wafer and form surface defects. In Comparative Example 2, the synergist is replaced by propylene glycol and sodium carboxymethyl cellulose. This combination may not provide the same fluidity optimization and viscosity adjustment capabilities as Example 3, resulting in increased surface roughness. In Comparative Example 3, the lack of lanthanum nitrate affects the formation or stability of the oxide layer, thereby affecting the polishing effect. In Comparative Example 4, after chitin was replaced by alumina, it failed to effectively promote the formation of the oxide layer, resulting in increased surface roughness. In Comparative Example 5, the replacement of the polishing pad material resulted in a decrease in mechanical properties and uneven current distribution, affecting the polishing effect. In Comparative Example 6, after graphene nanosheets and nano-silicon dioxide were replaced by carbon nanotubes, the mechanical properties and conductivity of the polishing pad were changed, resulting in an increase in surface roughness. In Comparative Example 7, the surface treatment method of the polishing pad was changed to immersing the polishing pad in an aqueous potassium persulfate solution, which may have resulted in reduced surface activity or other adverse effects, affecting the final polishing quality.

[0086] Performance Test 2 Resistivity Measurement

[0087] Test instrument: four-probe equipment;

[0088] Test sample: semiconductor silicon wafer polished by the methods of Example 3 and Comparative Examples 1-7;

[0089] Test method: Use ultrapure water and acetone to clean the silicon wafer to ensure that there are no impurities on the surface. Calibrate the four-probe equipment, take five different points on the silicon wafer surface for resistance measurement, and calculate the resistivity based on the measurement results. The test results are shown in Table 2.

[0090] Table 2 Resistivity measurement results

[0091]

[0092] The above measurement results show that the resistivity of Example 3 is lower, which means that the carrier migration inside the silicon wafer is smoother. This is because during the polishing process, the electrochemical reaction forms a uniform oxide layer on the surface of the silicon wafer, and the subsequent grinding and polishing effectively removes this oxide layer, leaving a relatively pure and structurally consistent silicon surface. The electrolyte in the electrolyte solution of Comparative Example 1 is replaced with sulfuric acid, phosphoric acid and hydrofluoric acid. Since these acids have strong corrosive effects, they may cause uneven corrosion on the surface of the silicon wafer, forming more surface defects and increasing the resistivity. The synergist in the electrolyte solution of Comparative Example 2 is replaced with propylene glycol and sodium carboxymethyl cellulose. These two synergists cannot effectively promote the electrochemical reaction like Example 3, resulting in incomplete removal of the oxide layer, and the residual oxide layer will increase the resistivity. The electrolyte solution of Comparative Example 3 does not contain lanthanum nitrate. Lanthanum nitrate plays an important role in electrochemical polishing. Its lack may lead to reduced efficiency of electrochemical reaction and insufficient surface treatment of silicon wafers, so the resistivity is high. In Comparative Example 4, the chitin in the electrolyte solution is replaced by alumina. Chitin helps to form a uniform oxide layer, while alumina does not have the same function, resulting in incomplete removal of the oxide layer and increased resistivity. In Comparative Example 5, the polyetheretherketone, polyimide, and polyphenylene sulfide in the polishing pad are replaced by polyurethane, polyethylene, and polyvinyl alcohol, respectively. These replacement materials cannot provide the same mechanical and electrical properties as Example 3, resulting in poor polishing effect and increased resistivity. In Comparative Example 6, the graphene nanosheets and nanosilica in the polishing pad are replaced by carbon nanotubes. Graphene nanosheets and nanosilica have unique advantages in improving the mechanical strength and conductivity of the polishing pad, and a single carbon nanotube cannot completely replace their role, resulting in increased resistivity. In Comparative Example 7, the plasma treatment step in the preparation of the polishing pad is replaced by immersion in a potassium persulfate aqueous solution. Plasma treatment can enhance the surface activity of the polishing pad and improve contact with the electrolyte solution, while potassium persulfate treatment results in incomplete surface treatment and high resistivity.

[0093] Performance Test 3: Film Thickness Uniformity Measurement

[0094] Test instrument: step meter;

[0095] Test sample: semiconductor silicon wafer polished by the methods of Example 3 and Comparative Examples 1-7;

[0096] Test method: Use ultrapure water and acetone to clean the silicon wafer to ensure that there are no impurities on the surface. Test immediately after cleaning to avoid re-oxidation of the silicon wafer surface due to oxygen molecules in the air. Use standard samples to calibrate the step meter, place the cleaned silicon wafer steadily on the measurement platform, ensure that the silicon wafer is in good contact with the platform, set the scanning path and scanning rate according to the area to be analyzed, start the step meter to scan, collect surface height data, and calculate the mean and standard deviation of the oxide layer thickness. The test results are shown in Table 3.

[0097] Table 3 Film thickness uniformity measurement results

[0098]

[0099] The film thickness uniformity measurement results show the uniformity of the oxide layer formed after the surface treatment of the semiconductor silicon wafer. If the oxide layer is not uniform, it may cause the device to work unstably or even fail. Uniform film thickness means that more precise control can be achieved in the semiconductor device manufacturing process, thereby improving the yield and consistency of the device. The film thickness uniformity of Example 3 is good. Example 3 achieves good film thickness uniformity by optimizing the electrolyte solution composition, polishing pad material and treatment method, and reasonably setting the polishing parameters. In Comparative Example 1, the electrolyte in the electrolyte solution is replaced by sulfuric acid, phosphoric acid and hydrofluoric acid, resulting in unstable oxide layer formation, thereby affecting the uniformity of film thickness. In Comparative Example 2, the replacement of the synergist changes the formation mechanism of the oxide layer during polishing, resulting in uneven film thickness. In Comparative Example 3, the lack of lanthanum nitrate affects the formation of the oxide layer, resulting in uneven film thickness. In Comparative Example 4, after chitin is replaced by aluminum oxide, it cannot effectively promote the formation of the oxide layer, resulting in uneven film thickness. In Comparative Example 5, the replacement of the polishing pad material leads to a decrease in mechanical properties and uneven current distribution, affecting the uniformity of film thickness. In Comparative Example 6, after graphene nanosheets and nano-silicon dioxide were replaced with carbon nanotubes, the mechanical properties and conductivity of the polishing pad were changed, resulting in uneven film thickness. In Comparative Example 7, the surface treatment method of the polishing pad was changed to immersion in a potassium persulfate aqueous solution, resulting in reduced surface activity and uneven film thickness.

[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for electrochemical mechanical polishing of a semiconductor silicon wafer, comprising the following steps: (1) Use ultrapure water and acetone to clean the silicon wafer. After cleaning, use nitrogen to blow dry the surface of the silicon wafer to ensure that the surface is clean; (2) Prepare electrolyte solution; (3) Fix the silicon wafer on the polishing head of the electrochemical mechanical polisher, with the surface to be polished facing the polishing table, lay the polishing pad with evenly distributed through holes on the polishing table, set the current density and polishing time, and adjust the rotation speed of the polishing table to ensure good contact between the silicon wafer and the polishing pad; (4) Turn on the power, start the polishing program, spray the electrolyte solution onto the surface of the polishing table, ensure that the electrolyte solution evenly covers the surface of the polishing pad and fills the through holes of the polishing pad to contact the surface of the polishing table, lower the polishing head, immerse the surface of the silicon wafer in the electrolyte solution and form an electrical contact with the polishing table, the silicon wafer and the electrolyte solution undergo an electrochemical reaction to form an oxide layer on the surface of the silicon wafer, start the rotation function of the polishing table, make the polishing head and the polishing table rotate relative to each other to perform grinding and polishing to remove the oxide layer; (5) After polishing, use deionized water to clean the surface of the silicon wafer to remove the residual electrolyte solution, and use nitrogen to blow dry the surface of the silicon wafer to prevent moisture from remaining; The electrolyte solution contains the following raw materials in parts by weight: 50-60 parts of electrolyte, 1-3 parts of surfactant, 2-4 parts of synergist, 0.06-0.1 parts of lanthanum nitrate, 0.1-0.5 parts of titanium dioxide, 0.5-1 parts of chitin, and 450-550 parts of deionized water; The electrolytes are citric acid, sodium sulfate, sodium gluconate and sodium phosphate, the surfactants are sodium lauryl sulfate and polyvinyl alcohol, and the synergists are polyethylene glycol and sodium silicate; The preparation method of the polishing pad comprises the following steps: (1) dispersing carbon nanotubes in a polyetheretherketone melt, and using ultrasonic treatment to ensure that the carbon nanotubes are evenly distributed in the melt, thereby obtaining a polymer melt 1; dispersing graphene nanosheets in a polyimide melt, and using ultrasonic treatment to ensure that the graphene nanosheets are evenly distributed in the melt, thereby obtaining a polymer melt 2; dispersing nanosilicon dioxide in a polyphenylene sulfide melt, and using a high-speed stirrer to stir the nanosilicon dioxide evenly in the melt, thereby obtaining a polymer melt 3; (2) mixing polymer melt 1, polymer melt 2, and polymer melt 3, and extruding them through a twin-screw extruder to obtain a composite sheet; (3) Use a high-precision laser punching machine to punch evenly distributed through holes on the composite sheet. The horizontal cross-sectional area of ​​the through holes is 8~15 mm 2 ; (4) The surface of the composite plate with through holes is activated by using plasma treatment technology to obtain the polishing pad.

2. The method according to claim 1, characterized in that The current density is 10-200 mA / cm², the polishing time is 10-60 minutes, and the rotation speed of the polishing table is 50-500 rpm.

3. The method according to claim 1, characterized in that The mass ratio of citric acid, sodium sulfate, sodium gluconate and sodium phosphate is 20:(15~25):(7~10):(3~5).

4. The method according to claim 1, characterized in that: The mass ratio of sodium dodecyl sulfate to polyvinyl alcohol is 1:0.3~0.

5.

5. The method according to claim 1, characterized in that: The mass ratio of polyethylene glycol to sodium silicate is 1:1.5~3.

6. The method according to claim 1, characterized in that The mass proportion of the carbon nanotubes in the polyetheretherketone melt is 0.3-0.6%, the mass proportion of the graphene nanosheets in the polyimide melt is 0.3-0.6%, and the mass proportion of the nano-silicon dioxide in the polyphenylene sulfide melt is 1-3%.

7. The method according to claim 1, characterized in that The mass ratio of the polymer melt 1, the polymer melt 2 and the polymer melt 3 is 1:0.7-0.9:0.7-0.

9.

8. The method according to claim 1, characterized in that: The plasma treatment conditions are set as follows: the gas is oxygen, the gas flow rate is 30-60 sccm, the vacuum degree is 0.5-5 Pa, the power is 200-600 W, and the treatment time is 5-20 minutes.

Citation Information

Patent Citations

  • A method for metal-assisted chemical etching and polishing of silicon wafers

    CN111128712B

  • Alkaline polishing method for silicon wafer, PERC battery and preparation method thereof

    CN114628252B

  • Electrochemical mechanical polishing method

    CN117943966A